Rural Livestock Insurance in St. Petersburg and St. Petersburg Province in Late 19th to Early 20th Century - D. A. Melnikova (Научный диалог)
This article analyzes the insurance activities of the Rural district councils (zemstvos) in St. Petersburg Province concerning the organization of voluntary livestock insurance during the last quarter of the 19th century. Utilizing archival data, administrative documentation, and journalistic publications as sources, the study highlights that the introduction of voluntary livestock insurance was driven by the necessity to enhance veterinary and sanitary oversight to prevent large-scale outbreaks of epizootics within the province. It emphasizes that livestock insurance aimed to compensate the population for losses incurred due to animal deaths. Starting in 1886, cattle were accepted for voluntary insurance based on standard and special valuations for specific breeds. The article presents key statistical data on livestock insurance outcomes across major cities and districts of the province from 1886 to 1892. The author concludes that voluntary zemstvo insurance primarily represented an attempt to mitigate the spread of dangerous epizootics in the province and served as a means to develop veterinary and sanitary support for the region. It is noted that the unprofitable results of the initial decade of zemstvo insurance activities led to the necessity of seeking new solutions, including the introduction of mandatory insurance. The article also points out that the losses incurred by the insurance system were attributed to the lack of mass livestock farming and large-scale agricultural enterprises in the province.